Comparison of Urethral Dilation with Amplatz Dilators and Internal Urethrotomy Techniques for the Treatment of Urethral Strictures - Karsli, Onur; Ustuner, Murat; Memik, Omur; Ulukaradag, Emre (Urology Journal, 2020)
Purpose: The most common option for the management of urethral stricture (US) is direct visual internal urethrotomy (DVIU), because it is an easy and minimally invasive technique but the low success and high recurrence rates of this technique make urologists research for different types of therapeutic alternatives in stricture treatment. In this study we aimed to compare the internal urethrotomy with amplatz dilation for the treatment of male US. Materials and Methods : A total of sixty patients, who have been operated due to urethral stricture were enrolled into this study. Group 1 was treated with amplatz renal dilators and the group 2 was treated with cold knife urethrotomy. All patients were evaluated for Qmax preoperatively and at the first, 3rd, 9th and 12th months postoperatively. Results: In the 3 month uroflowmetry results, mean Q max values were 15.6±2 ml/sec in amplatz group and 15.5±1.6 ml/sec in DVIU group. There was no statisticaly difference between the two groups. However the Q max values in the postoperative 9 and 12 months were significantly decreased in the DVIU group. In the DVIU group 9 recurrences (36%) appeared and 2 of these reccurrences were in the first 3 months, whereas in the amplatz group no recurrences appeared in the first 3 months. The urethral stricture recurrence rate up to the 12 month follow up was statistically significant for group 1 when it is compared with group 2. Conclusions: In our experience, amplatz dilation is a good option as the initial treatment for urethral stricture.